Media and Means of Speech Expression (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The study of means of speech expression is of great interest to journalists, since their use in media texts helps attract the attention of the audience and affects the perception of information. The secret of being a journalist is to write simply, clearly and at the same time interestingly. Expressive language can help a journalist convey material to the reader and express their opinion on what is happening. The stylistic encyclopedic dictionary of the Russian language notes: “Expressive means of language contribute to accuracy, logic, clarity, expressiveness, and ensure full perception of speech by the addressee.”.